The Significance of Reactive Oxygen Species and Antioxidant Defense System in Plants: A Concise Overview - Dumanović, Jelena; Nepovimova, Eugenie; Natić, Maja; Kuča, Kamil; Jaćević, Vesna (Frontiers in Plant Science, 2021)
In plants, there is a complex and multilevel network of the antioxidative system (AOS) operating to counteract harmful reactive species (RS), the foremost important of which are reactive oxygen species (ROS), and maintain homeostasis within the cell. Specific AOSs for plant cells are, first and foremost, enzymes of the glutathione-ascorbate cycle (Asc-GSH), followed by phenolic compounds and lipophilic antioxidants like carotenoids and tocopherols. Evidence that plant cells have excellent antioxidative defense systems is their ability to survive at H2O2 concentrations incompatible with animal cell life. For the survival of stressed plants, it is of particular importance that AOS cooperate and participate in redox reactions, therefore, providing better protection and regeneration of the active reduced forms. Considering that plants abound in antioxidant compounds, and humans are not predisposed to synthesize the majority of them, new fields of research have emerged. Antioxidant potential of plant compounds has been exploited for anti-aging formulations preparation, food fortification and preservation but also in designing new therapies for diseases with oxidative stress implicated in etiology.